Humor Trend in The Age of Social Media “It’s Just A Kidding” in The Qur’anic Perspectives of Surah Al-Hujurat Verse 11 (Jurnal Studi Al-Qur'an, 2023)
Humor is human nature to feel and share happiness. Nowadays, humor is one of the most popular forms of content, including pranks and roasting themed. This study attempts to review the humor trend in the study of Surah Al-Hujurat verse 11 and the ethics of humor as a form of communication. The research design uses a qualitative literature review study and a content analysis approach. The interpretation of Surah Al-Hujurat verse 11 was collected from several tafsir books, such as Tafsir Al-Maraghi, Tafsir Muyassar, Tafsir Al-Munir, Tafsir Fii Zhilalil Qur’an, Tafsir Al-Azhar, and Tafsir Al-Mishbah. The analysis results illustrate that humor practically is mubah, but some humor trends have made others the object of jokes with humiliating behaviour. Humor in Islam indeed considers the ethics of communication, including surah Al-Hujurat verse 11, which outlines the prohibition of humiliating others, including humor. Nevertheless, humor is permissible communication without turning others into objects of humiliating jokes. As a form of communication, humor requires ethics to avoid humiliating behaviour under the pretext of “it’s just kidding”, including qaulan sadida, qaulan maisura, qaulan layyina, and qaulan ma’rufa.